La genèse du village Archéologie de l'habitat groupé du haut Moyen Âge (Ve-XIIe siècles) dans le Centre-Est de la France actuelle - Guicheteau, Antoine; Marchaisseau, Vincent; Quiquerez, Amélie (Monographies et Actes de colloques, 2021)
Forty researchers and students gathered on November 27, 2018 for a simposion organized by the ARTEHIS "Landscape Factory" axis. We were gathered around the question of the formation of villages and more broadly of issues specific to the study of grouped habitats from the early medieval period. The communications made it possible to report on the diversity of approaches as well as advances in research in the Center-East. It is through the prism of chronological or regional syntheses, case studies resulting from preventive as programmed research or methodological reflections that the work of the various speakers fortunately supplemented by exchanges and remarks by the members of the audience put in particular the accent - again! - on the difficulties encountered in the characterization of the habitats uncovered, despite constantly updated field documentation. The debates were particularly interested in the contributions as at the limits of archeology concerning this problematic. The role of the church and the cemetery as well as that of the elites in the polarization of the habitat were repeatedly raised throughout the discussions. The questions of sustainability and the fixity of human occupations were also widely discussed, such as the nature of the specific activities grouped in dedicated sectors and their place in the village economy. Questions of settlement organization and terms of land use were also discussed and the importance of physical geography in the establishment of networks of habitats was underlined. In fact, there is numerous factors determining the human landscape in which the village is integrated